28th AIAA International Communications Satellite Systems Conference (ICSSC-2010) 2010
DOI: 10.2514/6.2010-8795
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Ad Hoc Networks Access For Aeronautical Communications

Abstract: There is an increasing interest in the current aeronautical context to offer new services for civil aircraft passengers. For example, airlines want to offer their customers the opportunity to access the Internet, to manage their mails, to watch video on demand, to access corporate VPNs.... All these services represent a new type of air-ground communications called APC (Aeronautical Passenger Communications) in the ATN (Aeronautical Telecommunication Network) context. In this paper, we will show how an aeronaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Consequently, it is dicult to obtain a delivery ratio close to 100% since it seems obvious that during this period, network partition exists. Previous studies on AANET like [2] found a reachable packet delivery ratio around 90%. It appears to be the maximum possible value of delivery ratio reachable with a publish / subscribe solution.…”
Section: General Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, it is dicult to obtain a delivery ratio close to 100% since it seems obvious that during this period, network partition exists. Previous studies on AANET like [2] found a reachable packet delivery ratio around 90%. It appears to be the maximum possible value of delivery ratio reachable with a publish / subscribe solution.…”
Section: General Resultsmentioning
confidence: 99%
“…As AANET is especially interesting for area where no ground infrastructures are available, as over oceans, we choose to reduce the scope to the transatlantic trac. That is why our simulations are taking into account aircraft whose latitude belongs to the interval [23,5 Physical/Mac layer Studies presented in this article deal with Publish / Subscribe service and not with the AANET feasibility which has been demonstrated in other studies like [2]. That's why it is not mandatory to have realistic physical and MAC layer.…”
Section: Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…G = G T G R , with G T and G R are antenna gains of transmitter and receiver. Thus, we have the absorption loss (in dB) PL dB = 92.44 + 10λ log( f GHz ) + 10λ log(d km ), where PL dB denotes the free space loss in dB, f GHz is the electromagnetic frequency in GHz, and d km is the distance between transmitter and receiver in km [28]. Let f GHz = 1 GHz and λ = 2, combine PL dB with the practical test results of the TTNT data link for the data rate [8], and then the propagation parameters can be summarized as Table 1.…”
Section: Propagation and Channel Modelsmentioning
confidence: 99%